Separation of Cotton-Seed Rushanka by Linear Dimensions and Aerodynamic Properties of the Components - Djuraev Anvar Djuraevich; Juraev Dadakhon Davlat o’g’li; Tursunov Sa’dullo Fayzullo o’g’li; Ziyodullaeva Sitorabonu Po’lot qizi (Genius Journals, 2023)
The article explains the work on the division of the seed bed into fractions according to the linear dimensions and aerodynamic properties of various components. In separators of different brands, we determined the fractional composition of the mermaid at different vertical speeds of the air flow and the fractional composition of the mermaid on the sections of seed sieves operating in the mermaid with fractions of different sizes, and also determined the fractional composition of the mermaid, which differed in the size of the particles that passed through the separator sieve (seeds according to ). The rise rate curves of the components (seed husk and kernel) are shown in the explanatory diagrams
Keywords: seed; rushanka; separator